Designing a Multi-purpose GSM Based Interactive Embedded Data-Acquisition System Providing Solutions for Fire Accidents - P Michael Preetam Raj; Rakesh Tirupathi; P Gopi Krishna; Jasti Sateesh; Vijay Krishna Balachander (International Journal of Electrical and Computer Engineering (IJECE), 2016)
The Data-Acquisition systems with remote accessibility are greatly demanded in industry and consumer applications. In this paper, a data-acquisition system which can save lives and property, based on GSM communication, accommodating a wide range of electronic devices is presented. The system has the special ability to automatically quench fire by spraying water during fire accidents, simultaneously informing the local fire station and the responsible persons as well, saving loss of life and property. Also the varying status can be instantaneously recorded and uploaded in internet, for failure analysis. By using a GPS receiver it is possible to acquire and display the images of the locations where there are fire accidents by decoding the text SMS data, which helps in continuously tracking the fire accident location using google maps, helping the fire engine to reach instantly. Also the cost-effectiveness of the overall system is proved. The embedded board acts as the main controller of this system which has a SIM card placed in it and thus communicates using GSM, making it accessible from anywhere in the world, providing a faster two-way data transfer between the Embedded system and the client, in real-time.